IMPLIKASI SISTEM KEKERABATAN DALIHAN NA TOLU (STUDI PADA KELUARGA URBAN MUSLIM BATAK ANGKOLA DI YOGYAKARTA) - Desniati Harahap (UIN Sunan Kalijaga Yogyakarta, 2016)
Urban Batak Angkola live in Yogyakarta are ethnics of North Sumatera.The nation has tradition and lokal wisdom, Batak Angkola have carried thedalihan na tolu system of kinship (mora, anak boru, kahanggi). The values in dalihan na tolu is very influential in social relationship of Batak Angkola and covered from all of life aspect. Area changing, philosophy and different local wisdom, life of urban Batak Angkola in Yogyakarta can be come about to cross cultural between Batak, Java, and another various ethnic in Yogyakarta. By virtue of those problem study there are quastion how the relationship between Batak Angkola tradition and Islam. And how urban Batak Angkola to implementation system of kinship in dalihan na tolu. To answer the problem, writer has gotten data by observation, interview, and documentation. The genre of research is field research by phenomenological sociology. This research yield show the traditional system and dalihan na tolu kinship of urban Batak Angkola in Yogyakarta are become different, when carring out of horja that implication dalihan na tolu system of kinship is changing from all fungtion in dalihan na tolu.